2019
DOI: 10.1016/j.lungcan.2018.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Nut and peanut butter consumption and the risk of lung cancer and its subtypes: A prospective cohort study

Abstract: Nut consumption has been associated with reduced cancer-related mortality, but evidence for a relation between nut intake and lung cancer risk is limited. We investigated the association between total nut, tree nut, peanut, and peanut butter intake and the risk of lung cancer and its subtypes in the Netherlands Cohort Study. Materials and Methods: In 1986, dietary and lifestyle habits of 120,852 participants, aged 55-69 years, were measured with a questionnaire. After 20.3 years of follow-up, 3720 subcohort me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The observed sex differences were also seen in previous analyses on nut consumption and cancer risk in the NLCS ( 50 ). One possible explanation might be differences in nut intake.…”
Section: Discussionsupporting
confidence: 81%
“…The observed sex differences were also seen in previous analyses on nut consumption and cancer risk in the NLCS ( 50 ). One possible explanation might be differences in nut intake.…”
Section: Discussionsupporting
confidence: 81%
“…Nut intake does not cause weight gain, but it improves body mass index and reduces the risk of obesity [6,17]. There has been a recent public increase in interest in the association between nut consumption and cancer [8,[18][19][20][21][22][23]. Recent studies have indicated a significant association between nut consumption and cancer risk and mortality [4,8].…”
Section: Discussionmentioning
confidence: 99%
“…Macadamia nut is a good source of tocopherols, tocotrienols, and squalene which can confer antioxidant and anticancer properties to consumers. Nieuwenhuisa and Brandt [166] conducted a large prospective cohort study and reported that total nut, tree nut, and peanut intake reduced the risk of small cell carcinoma in men.…”
Section: Cancermentioning
confidence: 99%